Shadow Bot: A Wearable-Controlled Humanoid Robot for Military Defence Applications - Manish Zore; Bhakti Yadav; P. V. Lokhande (Journal of Microprocessor and Microcontroller Research, 2025)
This research paper presents an innovative principle called “Shadow Bot,” a humanoid robot that can be driven by a wearable device, specially made to fulfil the requirements of military defence operations. The new system successfully mimics the actual movement of a soldier by using a specially designed motion-capture suit with built-in MPU6050 sensors to detect and translate the motion into the desired format. The robot uses servo motors for accurate joint articulation to produce smooth and natural motion, and it wirelessly communicates by using various modules, like nRF24L01, LoRa, and HC-12, for successful control over considerable distances. This innovative method significantly improves the safety of soldiers by making remote support easy for risky operations, like critical missions of bomb defusal, scouting, and rescue missions. The prototype, apart from showcasing successful replication of motion, also showcases significant potential for scalability, opening room for further use in the defence sector.